Caracterização acústica de caixas de ovos e similares - António P. O. Carvalho (2014)
It is not uncommon to find amateur music rehearsal rooms, coated with egg cartons, as it is an economical solution to allegedly improve it acoustically. This research characterized the acoustically the use of alveolar containers for storage and transportation of food supplies. Six distinct types of boxes for eggs and two fruit trays, were analyzed, a total of 21 different arrangements and materials. The results of sound absorption coefficients, measured in a reverberant chamber, are presented and discussed. In summary, were obtained NRC values between 0.20 and 0.70 and w between 0.10 and 0.65.